Field rat (Rattus argentiventer) population between near wooded area and free space area in paddy field at Kampung Belukar, Kodiang,Kedah Darul Aman / Nur Assyiffa Mohd Rozali - Mohd Rozali, Nur Assyiffa (Faculty of Plantation and Agrotechnology, 2016)
Rattus argentiventer from Muridae family is the common pest that attack the paddy field. This study are investigated about the field rat (Rattus argentiventer) population between near woody area and free space area in paddy field. It was conducted at Kampung Belukar, Kodiang, Kedah. This research was carried out by using Complete Randomized Design (CRD) for 5 weeks with 2 times ofcollection per week. The result from the research show that the population of Rattus argentiventer are high in paddy field near wooded area compared to free space area. Supported by SPSS analysis result, the data was not normally distributed (P < 0.05) while the Kruskal-Wallis Test result showed that the Rattus argentiventer was not significant (x² = 9.232; df =9; P > 0.05). Supported by t-test result, the data is no significant difference between near the wooded area and free space area at paddy field.